Pengembangan Komik Edukasi Detektif Sains Sebagai Media Pembelajaran Literasi Sains Sekolah Dasar - Oryzasativa, Tristaoryza; Sari, Tita Tanjung; Kadarisman (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2023)
Currently, the learning concept used in realizing 21st-century learning is that students need media or facilities in learning activities to become fun. Educational comics are an alternative used as learning media to improve the quality of education for the better. This study uses the R & D (Research and Development) research method with the research stage of the Borg and Gall model, which has been modified by Sugiono and consists of 7 research stages due to time, cost, and also the impact of the co-19 pandemic. This study aims to: (1) describe the development of the educational comic